EVALUACIÓN FÍSICO QUÍMICA Y PROTEICA DEL POLEN ALMACENADO EN COLMENAS DE Melipona seminigra, AMAZONAS, BRASIL. - BATISTA DA SILVA, Antonio (2022)
Bee’s pollen comes from the flowers of several species of plants. The grains are transported by worker bees to their nests (honeycombs) to be used as a source of nutrients. The objective of this study was to evaluate the microbiological control, the physical chemical composition and to analyze macro and micro minerals, as well as amino acids in dehydrated pollen hives of Melipona seminigra, in rainy periods (PLL) and dry periods (PS) in Amazonas, Brazil.The physical-chemical composition (proteins, lipids, carbohydrates, fibers and ashes) was performed by the AOAC methodology. In meliponícola pollen it was detected the presence of proteins (35,97 - 36,37 g/100g), lipids (22,37 - 29,66 g/100g), ashes (4,46 - 2,83 g/100g) and ratio carbon/nitrogen (8,94 - 8,28 g/100), also minerals like copper, iron, manganese, calcium, potassium, magnesium and phosphorus were present. In the pollen of the indigenous bees, both non-essential and essential amino acids were found. The results showedthat the meliponícola pollen did not present any contamination for bacteria and fungi that comply with the Brazilian legislation. The physical-chemical analysis confirmed that pollen has nutritional amounts that can be added to other ingredients, providing enrichment of fibers, minerals and proteins to foods at different ages of the population